Multiple Arbuscular Mycorrhizal Fungal Consortia Enhance Yield and Fatty Acids of Medicago sativa: A Two-Year Field Study on Agronomic Traits and Tracing of Fungal Persistence - Pellegrino, Elisa; Nuti, Marco; Ercoli, Laura (Frontiers in Plant Science, 2022)
Arbuscular mycorrhizal fungi (AMF) are promoted as biofertilizers due to potential benefits in crop productivity, and macro- and microelement uptake. However, crop response to AMF inoculation is context-dependent, and AMF diversity and field establishment and persistence of inoculants can greatly contribute to variation in outcomes. This study was designed to test the hypotheses that multiple and local AMF inoculants could enhance alfalfa yield and fatty acids (FA) compared to exotic isolates either single or in mixture. We aimed also to verify the persistence of inoculated AMF, and which component of the AMF communities was the major driver of plant traits. Therefore, a field experiment of AMF inoculation of alfalfa (Medicago sativa L.) with three single foreign isolates, a mixture of the foreign isolates (FMix), and a highly diverse mixture of local AMF (LMix) was set-up. We showed that AMF improved alfalfa yield (+68%), nutrient (+147% N content and +182% P content in forage) and FA content (+105%). These positive effects persisted for at least two years post inoculation, and were associated to enhanced AMF abundance in roots. Consortia of AMF strains acted in synergy, and the mixture of foreign AMF isolates provided greater benefits compared to local consortia (+20% forage yield, +36% forage N content, +18% forage P content, +20% total FA in forage). Foreign strains of Funneliformis mosseae and Rhizophagus irregularis persisted in the roots of alfalfa two years following inoculation, either as single inoculum or as component of the mixture. Among inoculants, F. mosseae BEG12 and AZ225C and the FMix exerted a higher impact on the local AMF community compared with LMix and R. irregularis BEG141. Finally, the stimulation of the proliferation of a single-taxa (R. irregularis cluster1) induced by all inoculants was the main determinant of the host benefits. Crop productivity and quality as well as field persistence of inoculated AMF support the use of mixtures of foreign AMF. On the other hand, local mixtures showed a lower impact on native AMF. These results pave the way for extending the study on the effect of AMF mixtures for the production of high-quality forage for the animal diet.